Analysis of Extension Worker Competencies and Factors Influencing The Readsi Program on Rice Farmers in Lasusua District, North Kolaka Regency - Erwin, Erwin; Haruna, Naima; Marwati Nuryanti, Dewi (Riwayat: Educational Journal of History and Humanities, 2025)
This study analyzes the competency of agricultural extension workers and the factors influencing the success of the READSI (Rural Empowerment and Agricultural Development Scaling Up Initiative) Program in increasing the income of rice farmers in Lasusua District, North Kolaka Regency. The competencies of extension workers studied include technical knowledge, communication skills, attitudes and work ethics, facilitation skills, and the use of information technology. Data were obtained through a survey of respondent farmers, then analyzed using multiple linear regression with the classical assumption test, t-test, F-test, and the coefficient of determination (R). The results showed that simultaneously the five variables of extension worker competency had a significant effect on activities to increase farmer income (F = 9.207; Sig. 0.000). Partially, communication skills, attitudes and work ethics, and facilitation skills had a significant positive effect, while technical knowledge and the use of information technology had no significant effect. The R value of 0.775 indicates that 77.5% of the variation in farmer income can be explained by extension worker competency, while 22.5% is influenced by other factors outside the model, such as policy, market access, and infrastructure. These findings emphasize the importance of improving the competency of extension workers, particularly in communication, work ethics, and facilitation skills. They also highlight the need for field mentoring and policy support to optimize the application of agricultural technology and innovation to increase rice farmer incomes in North Kolaka Regency.